Deep-ultraviolet polychromatic emission from three-dimensionally structured AlGaN quantum wells. (31st January 2017) - Kataoka, Ken; Funato, Mitsuru; Kawakami, Yoichi
Abstract: Three-dimensional (3D) AlGaN/AlN quantum wells (QWs) were fabricated on trench-patterned AlN templates using a regrowth technique based on metalorganic vapor phase epitaxy. The 3D structures are composed of planar (0001) facets, facets, and misoriented (0001) planes with bunched steps. Cathodoluminescence spectroscopy revealed double-peaked deep-ultraviolet (DUV) emissions: the shorter-wavelength emission was attributed to the (0001) facets, whereas the longer-wavelength emission arose from bunched step structures located around the bottom corner of the AlN trench, a region in which the AlGaN QWs possessed a relatively high Ga concentration and a thick well width compared with planar (0001) QWs.